Effect of potassium phosphate supplementation on perceptual and physiological responses to maximal graded exercise - Goss, F.; Robertson, R.; Riechman, S.; Zoeller, R.; Dabayebeh, I.; Moyna, N.; Boer, N.; Peoples, J.; Metz, K. (International Journal of Sport Nutrition and Exercise Metabolism, 2001)
This investigation evaluated the effect of oral potassium phosphate supplementation on ratings of perceived exertion (RPE) and physiological responses during maximal graded exercise tests (GXT). Eight highly trained endurance runners completed a GXT to anchor the Borg 15-point RPE scale and two double-blind counterbalanced GXTs. Subjects ingested either 4,000 mg á day-1 of phosphate (PHOS) or a placebo (PLA) for 2 days. Two weeks separated GXTs. Phosphate levels obtained immediately prior to the GXTs were greater in PHOS than PLA. No differences between PHOS and PLA were noted for the submaximal and maximal physiological responses. RPE for the overall body were lower during PHOS than PLA at intensities corresponding to 70-80% of VáO2max. This suggests that oral potassium phosphate supplementation mediates perceived exertion during moderately intense exercise.